Factores que limitan la correcta rendición de viáticos en los trabajadores de la red asistencial de Loreto EsSalud periodo 2021 – 2022 - Valera García, Diana Melissa (2024)
In health centers, the accountability of travel expenses is crucial to ensure transparency and efficiency in the use of funds managed by FONAFE. Proper documentation is essential to prevent irregularities. Therefore, this research aims to identify factors limiting the accurate accountability of travel expenses among employees in the Loreto Essalud healthcare network during the 2021 2022 period. Employing a quantitative observational research approach with a non-experimental descriptive design, the study involved 93 participants and utilized a 20-item instrument with a Cronbach's Alpha of 0.835. Findings revealed three primary constraints: inadequate knowledge of internal regulations, lack of formal payment receipts, and non-compliance with formal requirements in these documents. Insufficient familiarity with internal regulations was notably challenging, emphasizing the need for enhanced training. While time availability was not widely perceived as limiting, challenges in obtaining appropriate receipts and meeting formal requirements significantly impacted expense accountability for a substantial portion of respondents. These findings underscore the necessity of improving onboarding processes to ensure proper utilization of public resources.